464 Osteolytic Lesions of the Calcaneus in Paediatric Patients: Results from a Multicenter Study. (October 2012) - Frings, A; Andreou, D; Machacek, F; LieglAtzwanger, B; Zacherl, M; Windhager, R; Leithner, A
Abstract : Tumours of the calcaneus are exceedingly rare. X-rays are the standard examination tool and therefore we wanted to evaluate if X-rays alone were sufficient for proper diagnosis. Diard's classification was applied to define whether different types of lesions were characteristically distributed in the bone and in addition we analyzed whether type and/or duration of symptoms were possible indicators of malignancy. Sixteen patients (12 male, 4 female; mean age 15 years, range 8 to 20) were identified. The definitive diagnosis was simple bone cyst (n=10), aneurysmatic bone cyst (n=3), intraosseous lipoma (n=1) and Ewing's Sarcoma (n=2). Parameters analyzed were type and duration of symptoms, tentative diagnosis, operative procedure, recurrence rate, revision and localization of the lesion according to Diard. The main current complain was of pain without prior history of trauma in twelve cases. Symptoms preceded the definitive diagnosis for a mean time of seven (range 1 to 26) months. Discrepancies of the radiological and definitive diagnosis occurred in four of 16 cases. Applying Diard's system trabecular area number 6 was affected in 14 of 16 cases. We did not observe local recurrence for benign lesions. In each case of an osteolytic lesion of the calcaneus a malignant tumor must be ruled out and thus, plain X-rays in two planes alone are not sufficient and should therefore be followed by MRI. Applying the Diard system different types of lesions are not characteristically distributed in the bone. Increasing pain without previous trauma should always justify further examinations.